2010
DOI: 10.1002/pro.343
|View full text |Cite
|
Sign up to set email alerts
|

Critical biophysical properties in the Pseudomonas aeruginosa efflux gene regulator MexR are targeted by mutations conferring multidrug resistance

Abstract: The self-assembling MexA-MexB-OprM efflux pump system, encoded by the mexO operon, contributes to facile resistance of Pseudomonas aeruginosa by actively extruding multiple antimicrobials. MexR negatively regulates the mexO operon, comprising two adjacent MexR binding sites, and is as such highly targeted by mutations that confer multidrug resistance (MDR). To understand how MDR mutations impair MexR function, we studied MexR-wt as well as a selected set of MDR single mutants distant from the proposed DNA-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 55 publications
4
38
0
Order By: Relevance
“…(i) MexAB-OprM. Constitutively ex-pressed, the MexAB-OprM pump was the first RND system characterized in P. aeruginosa (10,13,388), although a link between the development of MDR and increased amounts of an OM protein, OprM, had previously been established in in vitro-selected mutants (389) and was also analyzed together with other overproduced 50-kDa OM proteins (11 MexAB-OprM-overproducing mutants can be readily generated by in vitro selection in the presence of an antibiotic(s) (11,389,402), and in vitro studies on reference strains have shown that any mutational event inactivating the mexR (also called nalB), nalC, or nalD gene or impairing the activity of their respective products (MexR, ArmR, and NalD [see Regulation of Multidrug Efflux Pumps, below]) results in the overexpression (Ն3-fold) of mexAB-oprM with a concomitant increase in resistance (2-to 16-fold MIC increases) to all the pump substrates compared to baseline levels, with nalC mutants being in general 2-fold more susceptible than the nalB and nalD mutants (393,(403)(404)(405)(406)(407)(408)(409). Similar findings were reported for phenotypically but non-genetically characterized multidrug-resistant mutants selected in vitro with various antibiotics (11,12,392,402,410,411).…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%
“…(i) MexAB-OprM. Constitutively ex-pressed, the MexAB-OprM pump was the first RND system characterized in P. aeruginosa (10,13,388), although a link between the development of MDR and increased amounts of an OM protein, OprM, had previously been established in in vitro-selected mutants (389) and was also analyzed together with other overproduced 50-kDa OM proteins (11 MexAB-OprM-overproducing mutants can be readily generated by in vitro selection in the presence of an antibiotic(s) (11,389,402), and in vitro studies on reference strains have shown that any mutational event inactivating the mexR (also called nalB), nalC, or nalD gene or impairing the activity of their respective products (MexR, ArmR, and NalD [see Regulation of Multidrug Efflux Pumps, below]) results in the overexpression (Ն3-fold) of mexAB-oprM with a concomitant increase in resistance (2-to 16-fold MIC increases) to all the pump substrates compared to baseline levels, with nalC mutants being in general 2-fold more susceptible than the nalB and nalD mutants (393,(403)(404)(405)(406)(407)(408)(409). Similar findings were reported for phenotypically but non-genetically characterized multidrug-resistant mutants selected in vitro with various antibiotics (11,12,392,402,410,411).…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%
“…The dimerization domain and the wHTH domain are connected by the helix2, H2, which maintains the relative orientations of the subdomains in the intersubunit dimer 48 . While mutational analyses on the dimerization helices have been shown to impact DNA interaction 54 , the key pattern recognizing the DNA promoter region is deployed in the wHTH motif 47 . Importantly, the MarR-DNA bound structures consistently shows that the H4 and H4', DNArecognition helices from wHTH motif binds to the major groove and that the Wings from each monomer subunit places specific MarR-contacts with the minor groove of the DNA (Fig.…”
Section: Marr-dna Bound Complexmentioning
confidence: 99%
“…The characteristic analysis of clinical specimens of P. aeruginosa overexpressing the MexAB-oprM pump, presented the list of spontaneous point mutations on MexR, that leads to MexR derepression of the operon 73 . Extensive biophysical analysis on the wild-type MexR show that mutations at the interface for dimer formation affect stability but with maintained structure 54 .…”
Section: Multidrug Resistant Mexr Variants Disengages Dna Binding Andmentioning
confidence: 99%
“…The residues involved in dimerization play a key role in maintaining the distance between the DNA recognition helices in the wHtH loops, which can ultimately affect the fidelity and strength of the protein-DNA interactions. Mutagenesis of the residues involved in the dimeric interface has been shown to cause low DNA binding affinity (Andresen et al, 2010). Furthermore, C-terminal deletion in MarR homologs decreases the ability to form dimers, which correlates with the attenuated DNA binding affinity and increased phenotypic resistance in E. coli (Linde et al, 2000).…”
Section: Crystal Structure Of Marr Homologuesmentioning
confidence: 99%